An engineering-economic model for CO2 pipeline transportation in China. (2014) - Zhao, Dongya; Zhang, Jian; Li, Zhaomin; Li, Qingfang; Liu, Haili; Lu, Shijian
Carbon capture, utilisation and storage (CCUS) can largely reduce the CO2 emission. Especially, CO2 enhanced oil recovery (CO2 -EOR) may reduce the costs of capture and storage and even create additional economic benefits. This technology has been increased quickly in China. A new CCUS demonstration project is being constructed in Shengli Oil Field by Sinopec. This paper is intended to report CO2 pipeline transportation which is an important link between capture and storage. The engineering-economic model is a base to evaluate the investment of the CO2 pipeline transportation. As an important part of CCUS, other parts' cost of CCU is also affected by transportation investment. The engineering-economic model of CO2 pipeline transportation will be constructed by considering Chinese real situations. By using this model, CO2 pipeline transportation investment cost can be estimated. The works presented by this paper are partly supported by Sinopec.